REMOTE SENSING FOR DETECTION OF WILT OF ERITHRINA SPECIES - M. D. SHEDHA, A. K. MISRA* AND (Indian Phytopathology, 2002)
Using multispectral aerial photographs (diapositives) on the scale 1 : 10,000 and viewed on the additive colour viewer with different light intensities, it was possible to detect wilted Erithrina patch. Out of the 13 combinations tried, the two best combinations were with band 11, III and IV with blue, red and green filters or blue, no filter and red filters respectively.